Enhancing Cryptocurrency Market Predictability Using Artificial Intelligence: A Platform for Predicting Prices and Trends of ‎Bitcoin, Ethereum, and Cardano - Suganya, Y .; Sree, Ch. Sudha; Kayalvili , S.; Jebadurai , D. Joel; Vani, M. Sowmya; Dhivya , S.; K, Sivakrishna; Reddy , R. Vijaya Kumar ‎ (International Journal of Basic and Applied Sciences, 2025)
Despite its rapid expansion in the last ten years, the cryptocurrency market remains highly volatile and unpredictable, creating difficulties for ‎both investors and market participants. Using artificial intelligence (AI) and machine learning techniques, this project seeks to ‎build a predictive model for cryptocurrency prices, which will focus on Bitcoin, Ethereum, and Cardano to solve market challenges. The ‎project aims to develop an end-to-end solution covering all stages of data management, which begins with setting up a real-time data ETL ‎pipeline to collect information from the Binance and Yahoo Finance APIs. The system places data into a structured database that holds historical price information as well as technical indicators. Historical data serves as the basis for training and testing machine learning models to ‎forecast price trends, which enhances cryptocurrency trading and investment decisions‎.